2020
DOI: 10.1111/jvim.15760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a collar‐mounted accelerometer for detecting seizure activity in dogs

Abstract: Background: The majority of dogs with idiopathic epilepsy continue to have seizures despite appropriate treatment.Objectives: To assess the use of a commercially available, collar-mounted accelerometer to detect generalized seizures in dogs.Animals: Twenty two client-owned dogs with idiopathic epilepsy.Methods: Six-month prospective clinical study during which dogs wore a collarmounted accelerometer. Seizure documentation was based on owner observations and video recordings. The accelerometer used a predefined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…A recent study using an accelerometer on a collar for detecting seizures in dogs revealed that generalized seizures could be detected with an accelerometer ( 33 ), which is consistent with our results. However, the overall sensitivity of identifying generalized seizures in this previous research was ~20%.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study using an accelerometer on a collar for detecting seizures in dogs revealed that generalized seizures could be detected with an accelerometer ( 33 ), which is consistent with our results. However, the overall sensitivity of identifying generalized seizures in this previous research was ~20%.…”
Section: Discussionsupporting
confidence: 92%
“…These devices not only measure physical activity in healthy dogs with reasonable accuracy (Chan et al 2005) but have been used to assess response to treatment in pruritic and osteoarthritic dogs (Brown et al 2010, Wernimont et al 2018. In epileptic dogs receiving AED therapy, CAMD has been used to measure baseline activity level (Barry et al 2021) and has been evaluated for use as a method to detect seizure activity (Muñana et al 2020). Our study is the first to use this device to objectively monitor activity changes in epileptic dogs in response to a prescribed activity treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous dog health collars available right now, but none has shown to be a reliable seizure detector. In a study by Munana et al ( 52 ) on a collar-mounted accelerometer in DWE, generalized seizures in dogs could be detected, but the overall sensitivity was low. In another study on a wearable automatic seizure detection system using acceleration data and the Mahalanobis distance in DWE with generalized tonic-clonic seizures (GTCS), the GTCS-detecting algorithm created for this study was effective in identifying all acceleration data of GTCSs as seizures and all acceleration data of daily activities as non-seizure activities ( 53 ).…”
Section: Subscalp Devices For Long-term Eeg Recordingsmentioning
confidence: 95%